2002
DOI: 10.1002/app.11321
|View full text |Cite
|
Sign up to set email alerts
|

Surface migration of carboxylic acid in styrene–butadiene rubber and its tribological consequences

Abstract: Surface migration of the carboxylic acids (C 10 H 21 COOH, C 11 H 23 COOH, C 12 H 25 COOH, C 15 H 31 COOH, C 16 H 33 COOH, and C 17 H 35 COOH) in styrene-butadiene rubber (SBR) matrix was investigated together with its influence on tribological properties of the vulcanisates. Macro-and microtribological properties were correlated with properties that come from carboxylic acid addition to the samples. A plastifying effect was characterized by a decrease of the rubber glass transition temperature measured by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…It is a consequence of limited solubility of low molecular weight components of rubber mix or products of their reactions, especially sulphur, carboxylic acids or their metal salts, respectively, in hydrocarbon matrix [5]. Together with a gradient structure of polymer materials [6] it facilitates tribochemical reactions, creating underestimated potential for modification of the surface of metal counterface.…”
Section: Resultsmentioning
confidence: 99%
“…It is a consequence of limited solubility of low molecular weight components of rubber mix or products of their reactions, especially sulphur, carboxylic acids or their metal salts, respectively, in hydrocarbon matrix [5]. Together with a gradient structure of polymer materials [6] it facilitates tribochemical reactions, creating underestimated potential for modification of the surface of metal counterface.…”
Section: Resultsmentioning
confidence: 99%
“…Each rubber mix was cured with 1 phr of dicumyl peroxide (DCP, 98% by wt purity, Merck-Schuhardt, Germany). A lower amount of DCP was applied this time in order to obtain more elastic material -closer to typical rubber than previously tested [17]. Specimens were vulcanised in a steel mould at 160 • C during time t max (ISO 3417) exceeded by 10 min to ensure that the process was complete.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [17,18,26,27], it was found that macroscale friction behaviour of rubber modified with low molecular weight additives is a function of two factors: (1) plasticization of rubber matrix, which causes an increase of friction force and (2) lubrication by a bloom, which is responsible for a decrease of friction force. If bloom on the surface of rubber is not thick enough to lubricate effectively, plasticization plays a dominant role in tribological behaviour, which results in increase of friction coefficient.…”
Section: Tribological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blooming process, frequently called additive surface migration, was thoroughly investigated experimentally and computationally 1–7…”
Section: Introductionmentioning
confidence: 99%